Livestock Genetic Improvements through Spermatogonial Stem Cell Transplantation Technology - Suyatno Suyatno (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2021)
Stem cells are unique cells that have the ability to differentiate into cells with specific functions and renew themselves to produce new stem cells. One type of stem cells that are actively studied is Spermatogonial Stem Cells (SSC). SSC is a unipotent cell that develops into spermatozoa in the mammalian testis. SSC can be transplanted into male testis recipients to improve the genetic quality of livestock and propagate valuable livestock. SSC transplantation procedure is started from the isolation of SSC from testis of the donor animal, in vitro culture of SCC for propagation or genetic modification, preparations of recipient males, and transplant SSC into recipient males to produce normal sperm that can fertilize the egg.  SSC transplantation technology has been successfully applied to large animals such as cattle, goats, sheep, buffalo, pigs, other mammals such as monkeys. SSC transplantation is promising biotechnology to improve livestock production in the near future. This review will describe the origins of the SSC, identification, and characterization of SSC, in vitro culture of SSC, and the application of SSC transplantation for genetic quality of livestock improvement.